AB0694 IS THERE ANY HETEROGENEITY OF SPONDYLOARTHRITIS DISEASE MANIFESTATIONS BETWEEN TWO ETHNIC SUBGROUPS?:A MULTICENTRE INTERNATIONAL COMPARATIVE STUDY BETWEEN INDIA AND UK. (2nd June 2020) - Jain, N.; Pandya, S.; Srivastava, P.; Chotalia, P.; Moorthy, A.
Abstract : Background: Pathogenesis of Spondyloarthritis (SpA) multifactorial and remains unclear. Various hypothesis have been postulated genetics, HLAB27, IL17, Gut microbiome and Biomechanical stress. Many of these factors can be attributed to ethnic background and environment. HLAB27 accounts for 20–25 % of total heritability and 40% of genetic risk while <10% of HLA-B27 carriers in general population develop SpA 1 . Higher faecal calprotectin levels in SpA compared to control point towards microscopic gut inflammation 2 . Thus dietary habits and geographical factors can influence pathogenesis of disease. We looked in clinical manifestations of SpA patients of two very different ethnic background Caucasians and Indians from UK and India to shed more light in understanding the disease Objectives: To study any differences in the clinical manifestations of SpA patients of two ethnic groups To compare outcome measure (BASDAI and ASDAS) between Caucasians and Indians To study the difference in disease activity between Indian patients and British Asians Methods: Multicentre observation study where data of SpA patients attending rheumatology clinics from two major teaching hospitals collected. In India data collected from Sheth VS Hospital and NHL Medical College, Gujarat and in United Kingdom from University Hospitals Leicester, NHS trust. Leicester has a multi-ethnic demography wherein almost 30% 3 of population is of south Asian ethnicity, making this study unique. Baseline demographic and clinical data was collected. Clinical and outcome measures compared to see any heterogeneity in disease manifestations. SPSS software used Results: Total 200 patients analysed with 148 Indians and 52 Caucasians. The Indian cohort was subdivided into British Asians (second generation Indians) and those form Gujarat, India We found Indian subgroups were younger with shorter disease duration. Comparison in Table 1 Conclusion: We found Caucasians had more HLAB27 positivity and extra-articular manifestation of uveitis however the Indian population has more enthesitis and peripheral arthritis. Enthesitis is initiated during a mechano-sensation and the cultural difference including style of footwear could probably be one of the factors explaining our findings inflammatory back pain has been reported to be higher in Indians compared to Caucasians which could be due to life style The fact that ASDAS CRP behaves similarly in Indian patients across the two countries and is more when compared to Caucasians might point towards overall higher burden of disease in Indian population To our knowledge this is a first study comparing clinical manifestations of SpA between Indians and Caucasians References: [1]Brown MAet al. Susceptibility to ankylosing spondylitis in twins: the role of genes, HLAand environment.Arthritis Rheum 1997;40: 1823–8 [2]J Simione, et al. Fecal Calprotectin, GutInflammation and SpA Archives of Medical Research. 2019;50:41-46 [3]http://www.ons.gov.uk/census Disclosure of Interests: Nibha Jain: None declared, Sapan Pandya: None declared, Puja Srivastava: None declared, Prashant Chotalia: None declared, Arumugam Moorthy Speakers bureau: Abbvie, Novartis, UCB, MSD